DEVELOPMENT OF A HANDHELD SOIL ANALYSIS SYSTEM FOR NPK NUTRIENT PROFILING UTILIZING NIR SENSOR TECHNOLOGY - G. S. Nhivekar; D.S. Jadhav; S. B. Kamble; B.T. Jadhav (The Bioscan, 2025)
This paper demonstrates a portable soil tester that utilizes an Arduino microcontroller and Near-Infrared (NIR) sensors for rapid and effective soil quality evaluation. Soil quality plays a critical role in agriculture, influencing crop yield and ecosystem health. Traditional soil testing methods are often time-consuming and require specialized equipment. The proposed portable soil tester aims to provide an affordable, user-friendly, and swift solution for farmers and researchers to assess key soil properties directly in the field. This study explores how NIR sensors can detect essential nutrients—Nitrogen (N), Phosphorus (P), and Potassium (K), collectively known as NPK nutrients—in soils. The research applies linear regression techniques to develop models that predict nutrient levels based on NIR sensor readings. The system displays soil NPK content results in high, medium, and low categories.